Theoretical, Numerical and Experimental Investigation of Vortex Shedding in a Novel Sub-Scaled Motor - R. Taherinezhad; G. Zarepour (Journal of Applied Fluid Mechanics, 2019)
Pressure oscillations are one of the important challenges of segmented solid rocket motors with high slenderness ratio. The reason for these oscillations can be searched in vortex shedding due to grain burning areas, holes and slots. In this paper, the pattern of four segments grain of space shuttle boosters and structure of Ariane5 sub-scaled motors have been used for evaluation of aeroacoustic pressure oscillations. First, the related parameters to scale down using Buckingham’s Pi-theorem were determined and then a sub-scaled 1:31 motor was designed and manufactured. Going on, Strouhal number in various grain forms and vortex shedding prediction criteria was discussed. Next, for a relative understanding of motor internal flow and vortex shedding formation, steady state computational fluid dynamic calculation was done in seven regression steps and finally, for validation of analysis and simulation, two static tests performed. Results show that various definitions for Strouhal number are useful only for primarily glance on vortex shedding and pressure oscillations and so CFD solution and the test program is inevitable for a correct understanding of the ballistic operational condition of the motor. In addition, despite aggress of pressure test data and grain-burning regression of sub-scaled motor to full-scale motor, the internal flow phenomenon may be different due to small-scale time and dimension with the full-scale motor.